THE RELATIONSHIP BETWEEN INCOME AND FAMILY SUPPORT TOWARD THE INCIDENCE OF STUNTING IN TODDLERS: THE RELATIONSHIP BETWEEN INCOME AND FAMILY SUPPORT TOWARD THE INCIDENCE OF STUNTING IN TODDLERS - Sunarmi, Sunarmi; Agustina, Fitria Fertha; Fuadi, Fauzan; Mulyono, Andi; Sari, Selly Puspita (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
Stunting is a major public health issue affecting child development, particularly in developing countries like Indonesia. This study aims to examine the relationship between parental income, family support, and the incidence of stunting in toddlers in Tempel Rejo Village, Kedondong Sub-district, Pesawaran Regency, Lampung Province. The study used an observational analytic design with a cross-sectional approach, involving 50 respondents selected through purposive sampling. Data were collected through self-administered questionnaires and analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) methods. The results revealed a significant relationship between income level and stunting (P = 0.005), with low-income families having a 6.926 times higher risk of stunting. Additionally, family support showed a significant association with stunting (P = 0.028), with families lacking support being 8.936 times more at risk. The Nagelkerke R Square value of 0.347 indicates that income and family support account for 34.7% of stunting cases, with family support being a stronger risk factor than income. These findings highlight the critical role of both financial stability and strong family support in preventing stunting and underscore the importance of education and intervention programs to empower families in addressing this issue.